GE_GERICHTE C/10959/2016 vom 16. Dezember 2019 - GE Cour de justice (2019)
BAIL À LOYER;DÉFAUT APPARENT;INFILTRATION DE SUBSTANCES;TRAVAUX D'ENTRETIEN(EN GÉNÉRAL);CONSIGNATION EN JUSTICE | CO.259; CO.259d